Evaluation of the SEVERITY of FACIAL and GENERAL TRAUMA in child and adolescent victims of traffic accidents. Issue 1 (January 2023) - Xavier, Thiago Brito; Silva Meira, Clarina Louis; Rodrigues de Lemos, Jeanne Gisele; Lacerda de Souza, Lucas; Ferreira, Diego Pacheco; de Vasconcelos Macedo, Diogo; Monnazzi, Marcelo Silva; Neto, Nicolau Conte; Rebelo Pontes, Hélder Antônio
Highlights: Evaluation of the FISS and TRISS SpO2 to obtain greater rigor in a standardized epidemiological profile of injury severity. More accurate determination of trauma severity in child and adolescent victims of traffic accidents for improved urgency and emergency care. Relation between the scales allows for better decisions on patient hospitalization, adequate treatment and the prevention of irreversible injuries.